2022
DOI: 10.1021/acs.langmuir.2c00255
|View full text |Cite
|
Sign up to set email alerts
|

Sliding and Rolling Motion of a Ferro-Liquid Droplet on the Hydrophobic Surface under Magnetic Influence

Abstract: The ferro-liquid droplet manipulation on hydrophobic surfaces remains vital for various applications in biomedicine, sensors and actuators, and oil–water separation. The magnetic influence of ferro-liquid droplets on the hydrophobic surface is elucidated. The mechanisms of a newborn droplet formation under the magnetic force are explored. The sliding and rolling dynamics of the ferro-liquid droplets are assessed for the various concentrations wt % of ferro-particles. High-speed recording and a tracker program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…the droplet position for a specific volume, as seen in Figure . Moreover, k also changes with droplet volume in a similar magnetic environment, contrasting the existing reports . Interestingly, for a particular drop volume, k is constant until s = 6 mm, as shown in Figure .…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations
“…the droplet position for a specific volume, as seen in Figure . Moreover, k also changes with droplet volume in a similar magnetic environment, contrasting the existing reports . Interestingly, for a particular drop volume, k is constant until s = 6 mm, as shown in Figure .…”
Section: Resultscontrasting
confidence: 68%
“…Moreover, k also changes with droplet volume in a similar magnetic environment, contrasting the existing reports. 31 Interestingly, for a particular drop volume, k is constant until s = 6 mm, as shown in Figure 11. As the droplet crosses the threshold distance of s = 6 mm, a step increment (marked by the dashed line) is observed for the shape factor k for all the droplet volumes.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…[8,15] However, in most research related to the development of these robots, their applicability is only demonstrated using magnets controlled by hand [8][9][10][11][12] or, in some cases, through mechanical stages. [13,16] Moreover, some studies that explore the locomotion of these robots in 3D environments rely solely on manually controlled magnets. [17,18] Electromagnets are essential for precisely controlling the locomotion of droplet robots.…”
Section: Introductionmentioning
confidence: 99%